Grocery retailing in Germany : situation, development and pricing strategies - Herrmann, Roland; Möser, Anke; Weber, Sascha; Justus Liebig University Giessen (My University, 2009)
Over the last four decades, the German food-retailing sector has been subject to continuous structural change. Most important has been the combination of increasing concentration with rising store size and the growing role of discounters implementing an aggressive EDLP pricing strategy. Thus, consumers have benefited from intensive price competition, despite the higher market share of leading food retailers. The analysis of market conduct, in terms of price formation and pricing strategies, reveals a typical situation of imperfect competition. The law of one price certainly does not hold for individual foods. Price levels and pricing strategies diverge substantially across firms and store types. There are successful retailers with an EDLP strategy, as well as others with a HiLo strategy. A major lesson to be learned from the German experience is that increasing concentration in food retailing does not necessarily imply that more market power is exerted at the expense of consumers. Competitive markets are compatible with a high level of concentration as long as a strong competitive fringe, for example discounters, challenges the large chains in food retailing.
Keywords: ddc:380